2002
DOI: 10.1161/01.cir.0000031802.58532.04
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Rate Control by Selective Vagal Stimulation Is Superior to Rhythm Regularization by Atrioventricular Nodal Ablation and Pacing During Atrial Fibrillation

Abstract: Background-Selective atrioventricular nodal (AVN) vagal stimulation (AVN-VS) has emerged as a novel strategy for ventricular rate (VR) control in atrial fibrillation (AF). Although AVN-VS preserves the physiological ventricular activation sequence, the resulting rate is slow but irregular. In contrast, AVN ablation with pacemaker implantation produces retrograde activation (starting at the apex), with regular ventricular rhythm. We tested the hypothesis that, at comparable levels of VR slowing, AVN-VS provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 39 publications
(42 reference statements)
0
45
0
Order By: Relevance
“…125 Additional data support the use of epicardial fat pad stimulation in animals with induced atrial fibrillation over standard atrioventricular nodal ablation and pacing. 126,127 In a recent pilot study, the effects of direct selective right vagus nerve electrical stimulation on LV function were examined in dogs with chronic HF using a new implantable system that also incorporates a right ventricular lead to monitor heart rate (CardioFit, BioControl Medical, Yehud, Israel). Results demonstrate that long-term (3 months) monotherapy with vagus nerve stimulation prevents progressive increases in LV end-diastolic volume, reduces LV end-systolic volume, and significantly increases LV ejection fraction.…”
Section: Could Direct Parasympathetic Stimulation Be Beneficial In Hf?mentioning
confidence: 99%
“…125 Additional data support the use of epicardial fat pad stimulation in animals with induced atrial fibrillation over standard atrioventricular nodal ablation and pacing. 126,127 In a recent pilot study, the effects of direct selective right vagus nerve electrical stimulation on LV function were examined in dogs with chronic HF using a new implantable system that also incorporates a right ventricular lead to monitor heart rate (CardioFit, BioControl Medical, Yehud, Israel). Results demonstrate that long-term (3 months) monotherapy with vagus nerve stimulation prevents progressive increases in LV end-diastolic volume, reduces LV end-systolic volume, and significantly increases LV ejection fraction.…”
Section: Could Direct Parasympathetic Stimulation Be Beneficial In Hf?mentioning
confidence: 99%
“…We have previously reported the benefits of slower ventricular rate during AF on LV diastolic function (17,24,26,27). In these studies, the improvement of diastolic parameters was demonstrated during selective atrioventricular nodal vagal stimulation by analysis of averaged values of diastolic parameters for Ͼ100 consecutive cardiac beats.…”
Section: Potential Benefit Of Slowing the Ventricular Rate During Afmentioning
confidence: 99%
“…We have recently reported (24,26,27) that slowing of ventricular rate by selective atrioventricular nodal vagal stimulation during AF improved both LV contractility and relaxation. It has been speculated that rapid ventricular rate with inadequate LV filling time during AF might be the major factor limiting cardiac performance (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are hemodynamic drawbacks because of the retrograde ventricular contraction. 11,12 Recently, lesions encircling rather than destroying the AVN were shown to result in acceptable junctional escape rhythm. 13,14 However, this technique needs further refinements and verification.…”
Section: Clinical Perspective P 2911mentioning
confidence: 99%